Implementasi Program PKK dalam Meningkatkan Pendidikan dan Ketrampilan Perempuan di Desa Naga Timbul - Utami, Ayu; Batu Bara, Beby Mashito; Angelia, Nina (Universitas Medan Area, 2025)
This study aims to analyze the implementation of the Family Empowerment and Welfare Program (PKK) in improving women's education and skills in Naga Timbul Village, Tanjung Morawa District. Implementation is an important stage in the policy process because it concerns the realization of the program to achieve the set goals. This study uses a descriptive qualitative approach and refers to Edward III's theory, which includes four indicators of policy success: communication, resources, disposition, and bureaucratic structure. The results of the study show that the implementation of the PKK program has not been optimal. Communication is considered quite good, and resources and disposition are adequate, but the bureaucratic structure is not well organized. In addition, many women in the village still have not shown improvement in education and skills. The main inhibiting factors come from low awareness, understanding, and community participation in participating in training, as well as the lack of maximum socialization from PKK management. Therefore, it is necessary to strengthen the role of cadres and increase community involvement to make the PKK program more effective.